Pengukuran Nilai Overall Equipment Effectiveness pada Divisi Painting di PT. AIM - Hermanto, Hermanto (Metris: Jurnal Sains dan Teknologi, 2016)
The research objective was to determine the effectiveness of the division of painting through the calculation of 3 (three) matrix OEE (availability, performance, quality) and identify the types of losses that cause low OEE elements that affect the performance of painting division. The method used is descriptive analysis, which describes the availability, performance and engine performance in the division of painting based on actual data and information by collecting, compiling, classifying, and analyzing in particular the information and data about the effectiveness of the painting division. The calculation result obtained from the average value of OEE is the average value of 95.33% availability painting division, the value of the average performance of 76.2%%, the average value of 97.4% quality. The value of these three factors resulted OEE values painting division 70.8%. The results of each measurement value losses were 7.58% (equipment failure), 9.52% (setup and adjustment), 74.29% (reduced speed), 8.62% (deffect losses). Of the three elements most significant OEE affect the low performance of the machine in the painting division perfomance rate is 76.2%. While these types contained in the largest loss Reduced speed (74.29%).